Temporal changes in neurotrophic factors and neurite outgrowth in the major pelvic ganglion following cavernous nerve injury - Hannan, Johanna L. (J Neurosci Res, 2015)
Despite nerve-sparing radical prostatectomy, nerve damage and erectile dysfunction (ED) prevails and preventing neurodegeneration is of great importance. Neurotrophic factors and neurite outgrowth were characterized in major pelvic ganglia (MPG) following bilateral cavernous nerve injury (BCNI). Young male Sprague-Dawley rats underwent sham or BCNI surgery and intracavernosal pressure to mean arterial pressure ratio (ICP/MAP) was measured 2, 7, 14, 21, 30 and 60 days following injury (n=8/group). MPG gene expression (qPCR) and Western blot was performed for glial cell line-derived neurotrophic factor (GDNF), nerve growth factor (NGF), neurturin (NRTN), neurotrophin-3 (NT3), neurotrophin-4 (NT4), brain-derived neurotrophic factor (BDNF), vascular endothelial growth factor (VEGF) and activating transcription factor 3 (ATF3). Additional rats were injured and MPGs removed 24h, 48h, 3 and 7 days following BCNI (n=3/group). MPGs were cultured in matrigel and neurite outgrowth measured. Erections were impaired early and improved by 60 days in BCNI rats. GDNF, NGF, BDNF and ATF3 gene expression was significantly increased and NT3 decreased in MPGs following BCNI (48h-21d; p<0.05). GDNF and NGF proteins levels were elevated in 48h BCNI. MPG neurite outgrowth from 24h and 48h BCNI was higher than sham (658±19μm; 607±24μm; 393±23μm, respectively, p<0.05). Further studies examining the roles of neurotrophic factors in modulating signaling pathways may provide therapeutic avenues for neurogenic-mediated ED.